Event-Level Differences in Quantity, Frequency, and Consequences of Cannabis Use by Modes of Use Among Sexual Minority Women and Gender Diverse Individuals - Dyar, Christina; Green, Elise; Rhew, Isaac C; Lee, Christine M (Journal of studies on alcohol and drugs, 2025)
A handful of studies have examined differences in the subjective effects and consequences of using different modes of cannabis (e.g., smoking vs. vaping) at the daily level. However, results have been mixed, and recent research suggests that there may be individual-level differences in these effects based on how often individuals use each mode. We aimed to determine whether within-person associations between mode of cannabis use (i.e., smoking, vaping plant material, vaping concentrates, dabbing, edibles, multiple modes) and quantity, subjective intoxication, consequences, contexts of cannabis use, and co-use with alcohol or tobacco varied based on how often individuals used each mode. We used data from a 30-day ecological momentary assessment study of cannabis use with 338 sexual minority women and gender diverse young adults assigned female at birth, populations at high risk for cannabis use disorder. Several associations between mode of cannabis use and outcomes differed based on how frequently individuals used each mode. People who used edibles less frequently experienced more consequences when using edibles compared with smoking cannabis, whereas people who used edibles more frequently did not. People who used multiple modes more frequently took fewer hits when using multiple modes, whereas those who used multiple modes less frequently did not. Analyses suggest that frequency, quantity, and consequences of some modes of use differed based on how frequently individuals used each mode. Further research is needed to identify protective behavioral strategies that may be utilized by individuals who use particular modes more often.